2005
DOI: 10.1189/jlb.0505253
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses and sudden infant death syndrome: genetic, developmental, and environmental risk factors

Abstract: Despite the success of the campaigns to reduce the risk of sudden infant death syndrome (SIDS), it still remains the major cause of postneonatal mortality. The incidence of SIDS is higher among ethnic groups in which there are also high incidences of serious infectious diseases. The risk factors for SIDS parallel those for susceptibility to infection, and recent data have provided evidence to support the mathematical model of the common bacterial toxin hypothesis. One current hypothesis for the etiology of SID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 169 publications
3
77
0
Order By: Relevance
“…Necrotizing enterocolitis, an intestinal disease that occurs frequently in preterm newborns, is thought to be due to a robust intestinal epithelial inflammatory responses to bacterial infection (9). Sudden infant death syndrome (SIDS) is another newbornrelated disease, and both infections in the 2 weeks before death occur in Ͼ40% of SIDS infants and increased IL-6 in the cerebrospinal fluid have been reported (41)(42)(43).…”
Section: 01) Data Are Presented As Mean Values (ϯSem) (D) Lethal mentioning
confidence: 99%
“…Necrotizing enterocolitis, an intestinal disease that occurs frequently in preterm newborns, is thought to be due to a robust intestinal epithelial inflammatory responses to bacterial infection (9). Sudden infant death syndrome (SIDS) is another newbornrelated disease, and both infections in the 2 weeks before death occur in Ͼ40% of SIDS infants and increased IL-6 in the cerebrospinal fluid have been reported (41)(42)(43).…”
Section: 01) Data Are Presented As Mean Values (ϯSem) (D) Lethal mentioning
confidence: 99%
“…It is the principal cytokine secreted during the acute-phase inflammatory responses to damage in tissues. IL-6 has been found in high levels in some SIDS cases and infants who died of bacterial sepsis and meningitis [22,35,49]. The similar levels of IL-6 highlight possible similarities between SUDI cases and deaths due to infections and could support a contributory role of infections and subsequent immune response in causing SUDI.…”
Section: Inflammation and Possible Contributions To Infant Demisementioning
confidence: 97%
“…The similar levels of IL-6 highlight possible similarities between SUDI cases and deaths due to infections and could support a contributory role of infections and subsequent immune response in causing SUDI. However, the degree of inflammation required for lethality is still uncertain [33,35,36].…”
Section: Inflammation and Possible Contributions To Infant Demisementioning
confidence: 99%
See 1 more Smart Citation
“…The italics are ours, and it is to suggest that more is known than is suggested in this blank statement. We and our associates (Goldwater 2001, Bettelheim et al 1989,1990, Goldwater & Bettelheim 2002, Pearce et al 1999a, 1999b, 2004 as well as others (especially Drucker et al 1992, Bettiol et al 1994, Blackwell et al 2005, Jakeman et al 1991, Malam et al 1992, Sayers et al 1995 have shown that toxigenic organisms notably ones normally considered nonpathogenic commensals may well have an important role to play in the death of these infants. There is strong evidence to support the hypothesis that SIDS is triggered by a dysregulated response to infection or microbial toxins.…”
Section: ) Evidence For Infection and Inflammation In Sids Pathogenesismentioning
confidence: 99%